Advancing species-based predictions of Nature’s contributions to people - Pierre-Louis Rey; Antoine Adde; Nathan Külling; Anthony Lehmann; Antoine Guisan (Trends in Ecology & Evolution, 2026)

Identifying robust area-based conservation strategies to secure ecosystem service provision under uncertainties - Benjamin Black; Antoine Adde; Nathan Külling; Carlson Büth; Manuel Kurmann; Anthony Lehmann; Florian Altermatt; Antoine Guisan; Adrienne Grêt-Regamey (Journal of Environmental Management, 2026)

Sub-seasonal forecasting of thermal stress for Swiss river fishes during heatwaves - Adeline Bonaglia; Chenyu Shen; Ryan S. Padrón; Konrad Bogner; Fabian Fopp; Aurélie Rubin; Jean-François Rubin; Antoine Adde; Antoine Guisan; Camille Albouy; Loïc Pellissier (Ecological Modelling, 2025)

How Vulnerable Are Plants to Land‐Use and Climate Changes? Comparing Current and Future Distributions at the Regional Scale According to Native and Red List Statuses - Arthur Sanguet; Nicolas Wyler; Blaise Petitpierre; Pascal Martin; Michelle Price; Antoine Adde; Anthony Lehmann (Journal of Biogeography, 2025)
Aim Future species distributions were modelled to assess the distributional changes of 1692 plant species according to several scenarios. Species vulnerability was calculated according to their red list and native statuses using a new index to better understand the most vulnerable groups of species to future conditions and improve conservation actions. Location Greater Geneva region between France and Switzerland. Time Period From present to 2050. Major Taxa Studied A total of 1692 species of plants from all major groups. Methods Two different species distribution models were created to combine the effect of climate change at the continental scale and land‐use changes at the regional scale in 2050. Two scenarios of climate change were used (optimistic and pessimistic) and one business‐as‐usual land‐use–land‐cover scenario. Current and future distributions were compared using six spatial indicators combined to create a new vulnerability index to global changes. Results More than one‐third of all species assessed showed at least a moderate vulnerability, and more than 10% showed a high vulnerability to global changes, mostly composed of native species. Most exotic species showed moderate benefits to global changes, and one‐third were associated with high benefits. Pessimistic scenarios of climate change exacerbated the trends identified under optimistic scenarios and were associated with higher vulnerability for native species and higher benefits for exotic ones. No clear pattern was found when comparing species vulnerability according to their red list status, questioning its ability to preserve species in the long term. Main Conclusions Native species are more vulnerable to global changes, while exotic species benefit from them. Climate is the main driver of future distributional changes in the study area. Current levels of threat fail to inform us of species vulnerability to future conditions, questioning their relevance and supporting the assessments of similar studies to identify the most vulnerable species.

Projecting Untruncated Climate Change Effects on Species' Climate Suitability: Insights From an Alpine Country - Antoine Adde; Nathan Külling; Pierre‐Louis Rey; Fabian Fopp; Philipp Brun; Olivier Broennimann; Anthony Lehmann; Blaise Petitpierre; Niklaus E. Zimmermann; Loïc Pellissier; Florian Altermatt; Antoine Guisan (Global Change Biology, 2024)
Climate projections for continental Europe indicate drier summers, increased annual precipitation, and less snowy winters, which are expected to cause shifts in species' distributions. Yet, most regions/countries currently lack comprehensive climate‐driven biodiversity projections across taxonomic groups, challenging effective conservation efforts. To address this gap, our study evaluated the potential effects of climate change on the biodiversity of an alpine country of Europe, Switzerland. We used a state‐of‐the art species distribution modeling approach and species occurrence data that covered the climatic conditions encountered across the full species' ranges to help limiting niche truncation. We quantified the relationship between baseline climate and the spatial distribution of 7291 species from 12 main taxonomic groups and projected future climate suitability for three 30‐year periods and two greenhouse gas concentration scenarios (RCP4.5 and 8.5). Our results indicated important effects of projected climate changes on species' climate suitability, with responses varying by the taxonomic and conservation status group. The percentage of species facing major changes in climate suitability was higher under RCP8.5 (68%) compared to RCP4.5 (66%). By the end of the century, decreases in climate suitability were projected for 3000 species under RCP8.5 and 1758 species under RCP4.5. The most affected groups under RCP8.5 were molluscs, algae, and amphibians, while it was molluscs, birds, and vascular plants under RCP4.5. Spatially, by 2070–2099, we projected an overall decrease in climate suitability for 39% of the cells in the study area under RCP8.5 and 10% under RCP4.5, while projecting an increase for 50% of the cells under RCP8.5 and 73% under RCP4.5. The most consistent geographical shifts were upward, southward, and eastward. We found that the coverage of high climate suitability cells by protected areas was expected to increase. Our models and maps provide guidance for spatial conservation planning by pointing out future climate‐suitable areas for biodiversity.

Broadening the horizon in land use change modelling: Normative scenarios for nature positive futures in Switzerland - Benjamin Black; Antoine Adde; Daniel Farinotti; Antoine Guisan; Nathan Külling; Manuel Kurmann; Caroline Martin; Paula Mayer; Sven-Erik Rabe; Jan Streit; Harry Zekollari; Adrienne Grêt-Regamey (Regional Environmental Change, 2024)
Within scenario-based research of social-ecological systems, there has been a growing recognition of the importance of normative scenarios that define positive outcomes for both nature and society. While several frameworks exist to guide the co-creation of normative scenario narratives, examples of operationalizing these narratives in quantitative simulation modelling are still limited. To address this gap, this paper presents an example of how aspects of normative scenarios can be realized within a spatial model of land use and land cover change. This is achieved through a combination of data-driven approaches to encapsulate scenario-specific differences in local and global scale phenomena, as well as iterative expert elicitation to quantify descriptive trends from narratives. This approach is demonstrated with a case study simulating five scenarios of landscape change (three normative and two exploratory) in Switzerland between 2020 and 2060. The resulting maps of future land use and land cover exhibited distinct variations between the scenarios, notably with regard to the prevalence of areas of heterogeneous semi-natural land, such as alpine pastures and grassland, often considered culturally emblematic of Switzerland. While the simulation results were generally consistent with the outcomes expressed in the scenario narratives, following a process of expert feedback, we reflect that there are clear challenges in leveraging such results to elicit further discussions as to the desirability and plausibility of future scenarios. Specifically, the need to summarize spatial simulations in a manner that is easily interpretable and encourages consideration of the broader patterns of change rather than focusing on fine-scale details.

Re-considering the status quo: Improving calibration of land use change models through validation of transition potential predictions - Benjamin Black; Maarten J. van Strien; Antoine Adde; Adrienne Grêt-Regamey (Environmental Modelling & Software, 2023)

Projected effects of climate change on the distribution and abundance of breeding waterfowl in Eastern Canada - Antoine Adde; Diana Stralberg; Travis Logan; Christine Lepage; Steven Cumming; Marcel Darveau (Climatic Change, 2020)

Climatic gradients along the windward slopes of Mount Kenya and their implication for crop risks. Part 2: crop sensitivity - Nathalie Philippon; Christian Baron; Joseph Boyard‐Micheau; Antoine Adde; Christian Leclerc; Caroline Mwongera; Pierre Camberlin (International Journal of Climatology, 2016)
Mount Kenya is an equatorial mountain whose climatic setting is fairly simple (two rainy seasons in March–May, the Long Rains, and October–December, the Short Rains) though concealing significant spatial variations related to elevation and aspect (part I, Camberlin et al. , 2014). This part II is dedicated to the sensitivity of sorghum yields to climate variability in space and time, with a focus on the intra‐seasonal characteristics of the rainy seasons. To that aim we use the crop model SARRA ‐H calibrated for the region and fed with rainfall, temperature, wind speed, humidity and solar radiation data over the period 1973–2001 at three stations located on the eastern slopes of Mount Kenya. The crop model is run independently for the two rainy seasons. Four groups of simulations are conducted by varying the initialization date of the simulation, the sowing dates and the type of soil, in order to test sorghum sensitivity to water availability. Evidence is found that potential sorghum yields are dominantly controlled by variations in seasonal rainfall amounts: mean yields are higher at higher and wetter locations, and are higher during the wettest rainy season and years. However, beyond this apparent simplicity, more complex aspects emerge of the crop–climate relationships. First, the yield–elevation relationship is altered at high elevation due to lower temperature. Second, despite a strong link with the seasonal rainfall amounts, we evidence an underlying role of some intra‐seasonal rainfall characteristics such as the number of rainy days (itself mainly determined by the rainy season duration) or the occurrence of long dry spells. Third, unseasonal rains occurring after the end of the rainy season, especially after the Short Rains, play a role in final crop yield. Fourth, variations of climate variables such as solar radiation by modulating the potential evapotranspiration concur to yield variations at the wettest locations.